2021
DOI: 10.1007/s11356-021-15557-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of reservoir operation on the spatiotemporal variation in nitrogen forms in the post-Three Gorges Dam period (2004–2016)

Abstract: Nitrogen (N) is an essential nutrient limiting life, and its biochemical cycling and distribution in rivers have been markedly affected by river engineering construction and operation. Here, we comprehensively analyzed the spatiotemporal variations and driving environmental factors of N distributions based on the long-term observations (from 2004 to 2016) of seven stations in the Three Gorges Reservoir (TGR). In the study period, the overall water quality status of the river reach improved, whereas N pollution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…DIN (77.9 ± 64.1 μmol/L) accounted for 71.6% of TDN, which was slightly lower than that in 1997 (87.5%), 2009–2010 (90.4%), and 2016 (93.9%) . The average concentration of DON (19.8 ± 28.1 μmol/L) was approximately twice as high as that in previous years (6.7–12.7 μmol/L), while NO 3 – –N (77.9 ± 64.1 μmol/L) fell within the range from 2003 to 2016 (75.3–102.8 μmol/L) and higher than the natural background (0.08–0.16 N mg/L). , Additionally, NO 3 – –N dominated the composition of DIN, accounting for approximately 89–94% during wet season. , …”
Section: Results and Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…DIN (77.9 ± 64.1 μmol/L) accounted for 71.6% of TDN, which was slightly lower than that in 1997 (87.5%), 2009–2010 (90.4%), and 2016 (93.9%) . The average concentration of DON (19.8 ± 28.1 μmol/L) was approximately twice as high as that in previous years (6.7–12.7 μmol/L), while NO 3 – –N (77.9 ± 64.1 μmol/L) fell within the range from 2003 to 2016 (75.3–102.8 μmol/L) and higher than the natural background (0.08–0.16 N mg/L). , Additionally, NO 3 – –N dominated the composition of DIN, accounting for approximately 89–94% during wet season. , …”
Section: Results and Discussionmentioning
confidence: 82%
“…The significant negative correlation between NO 3 – –N/TDN and NH 4 + –N/TDN ( p < 0.01, r = −0.418, Figure a) implied the occurrence of transformation between NH 4 + –N and NO 3 – –N. Previous studies also showed that NH 4 + –N is easily converted to NO 3 – –N by the ammonia oxidation process, resulting in an increase in NH 4 + –N and a decrease in NO 3 – –N in TGR river water . Compared to YL, the hydrological process of the Chongqing-TGD reach is more vulnerable to the regulatory impacts of the TGD .…”
Section: Results and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Since the operation of the Three Gorges Dam (TGD), the hydrodynamics and nutrient load have been clearly affected. , Meanwhile, algal blooms occur frequently in the backwater zone of 22 tributaries during the wet season . Surface water quality in the TGR basin has been widely concerning .…”
Section: Introductionmentioning
confidence: 99%